Inclusive business market scoping study in the people republic of China. (Metro Manila, Philippines Asian Development Bank, 2018)
This case study, supported by the Asian Development Bank, presents the application of a SEAP framework for developing cost effective energy plans for Pyuthan district. It also highlights the benefits of access to cleaner energy in terms of social well being, reduction in the emission of local pollutants and greenhouse gas, and reducing energy inequality The report explains the current state of inclusive business (IB) models from the PRC, drawing from domestic and international company examples and practices. Key characteristics of IBs in terms of sector, size, and business model, and challenges facing these IBs are discussed. It also presents opportunities for IB to build on existing government programs, and proposes actions various stakeholders can take to promote the growth of IB in PRC.
Keywords: Economic development; China -- Economic conditions; Economic development -- Social aspects -- China; Electronic books